2019
DOI: 10.3889/oamjms.2019.288
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Treatment of Lymphatic Leakage Post Appendectomy: Case Report

Abstract: BACKGROUND: Postoperative lymphatic complications are not common, and lymphatic leakage complication post appendectomy (LLCPC) is even rarer. However, the number of this operation is high so LLCPC can occur. CASE REPORT: Here, we report a female patient post appendectomy with severe chylous ascites. This patient underwent six operations. A leakage point at the right iliac-fossa, which was embolized successfully after two sessions, was spotted during intranodal lymphangiography. After 6 months, the ascite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It has been reported that the NBCA iodised oil diluent was mixed evenly at a ratio of 1:2 [ 24 ]. In our study, NBCA iodised oil diluent was used and mixed evenly at a ratio of 1:3 to 1:4.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the NBCA iodised oil diluent was mixed evenly at a ratio of 1:2 [ 24 ]. In our study, NBCA iodised oil diluent was used and mixed evenly at a ratio of 1:3 to 1:4.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the NBCA iodized oil diluent was mixed evenly at a ratio of 1:2 [24] . In our study, the NBCA iodized oil diluent was used and mixed evenly at a ratio of 1:3 to 1:4.…”
Section: Discussionmentioning
confidence: 99%